Perovskite optoelectronic devices with defect passivation
By introducing a passivator into a perovskite semiconductor, using the combination of passivation groups and induction groups, the trap-mediated non-radiative loss problem in perovskite semiconductors is solved, and a high-efficiency perovskite LED is achieved.
Patent Information
- Application Number
- CN202080032884.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-01
- Filing Date
- 2020-02-28
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2040-02-28
AI Technical Summary
In the prior art, solution-treated perovskite semiconductors suffer severe trap-mediated non-radiation losses, resulting in efficiency limitations of photovoltaics and LEDs.
By introducing a passivating agent containing passivation groups and induction groups, defect passivation in perovskite semiconductors is improved and non-radiative recombination losses are reduced.
The abnormally high external quantum efficiency (EQE) of perovskite LEDs is achieved at 21.6%, and high efficiency is maintained at high current density, significantly improving the performance of perovskite optoelectronic devices.
Smart Images

Figure FDA0005285593550000011 
Figure GDA0005272259330000021 
Figure GDA0005272259330000022
Abstract
Description
Field of the Invention
[0001] The present invention relates to metal halide perovskite optoelectronic devices and organic passivators. In particular, the present invention relates to metal halide perovskite optoelectronic devices in which defects have been passivated by introducing passivating molecules in which the hydrogen bonding ability has been reduced. Background of the Invention
[0003] Perovskites, especially metal halide perovskites, have attracted increasing attention in the past decade as promising functional materials for optoelectronic devices such as solid-state light-emitting devices and photovoltaic devices. Metal halide perovskites are low-cost solution-processable materials with excellent intrinsic properties, such as wide tunability of band gap, defect tolerance, high photoluminescence quantum efficiency, and high emission color purity.
[0004] To realize efficient perovskite-based light-emitting diodes (PeLEDs), extensive attempts have been made to increase the radiative recombination rate by confining electrons and holes. These confinement attempts include the use of ultrathin emission layers, the fabrication of nanoscale polycrystalline parts, the design of low-dimensional or multi-quantum well structures, and the synthesis of perovskite quantum dots. As a result, the EQE values of PeLEDs have been improved from less than 1% to about 14%.
[0005] In addition to increasing the radiative recombination rate, reducing non-radiative recombination is equally important for improving device performance. Unfortunately, state-of-the-art solution-processed perovskite semiconductors suffer from severe trap-mediated non-radiative losses, which have been identified as the main efficiency limiting factor for both photovoltaics (PV) and LEDs. It is generally believed that the trap states are associated with ionic defects (e.g., halide vacancies). Defect passivation by molecular passivators (PAs) that can chemically bond to defects is an attractive approach to address this problem. Several functional groups (e.g., –NH2, P=O) have been identified to passivate perovskite semiconductors for photovoltaic applications. It was found that these PAs exhibited strong structure-dependent properties, even though they had the same functional groups for interacting with perovskite defects. These functional groups have also been used to improve the efficiency of LEDs, with limited success so far. For example, it has been reported that treatment with trioctylphosphine oxide (TOPO) in green PeLEDs resulted in only moderate EQE enhancement.
[0006] A recently published article, "Perovskite light-emitting diodes based on spontaneously formed submicrometre-scale structures" (Cao et al., October 11, 2018, Vol. 562, Nature 249) discloses the introduction of amino acid additives into perovskite precursor solutions, and reports an EQE of over 18% for 5-aminovaleric acid (5AVA). Similar results have been claimed for even longer chain length amino acids (6-aminohexanoic acid (6AcA) and 7-aminoheptanoic acid). The positive effect is attributed to the additive that promotes the formation of submicrometer-scale structures, which is described as having a passivating effect.
[0007] Although improvements have been made, the negative effects of non-radiative recombination must be reduced to a considerable degree in order to make optoelectronic devices based on metal halide perovskite materials commercially attractive compared to alternative technologies such as polymer LEDs and organic LEDs. SUMMARY OF THE INVENTION
[0009] While progress has been made in providing efficient optoelectronic devices based on perovskite materials, non-radiative recombination losses remain a significant issue in delivering commercially attractive devices.
[0010] It is an object of the present invention to provide a method and a device which overcome the disadvantages of the prior art.
[0011] This is achieved by an optoelectronic device as defined in claim 1 , claim 9 , claim 13 and claim 17 and by a method as defined in claim 26 .
[0012] According to one aspect of the present invention, there is provided an optoelectronic device based on a perovskite material comprising a passivating agent, the passivating agent comprising at least one passivating molecule. The passivating molecule is a hydrocarbon compound comprising at least one passivating group PG, at least one sensing group IG and an alkyl chain, which are arranged as a structural unit according to the following general formula:
[0013]
[0014] wherein n is between 1 and 4. The passivating molecule may comprise at least two passivating groups and two sensing groups, wherein each passivating group has a corresponding sensing group at a distance corresponding to a value of n between 1 and 4. Alternatively, the purification molecule comprises at least two passivating groups and one sensing group associated with the two passivating groups, wherein each passivating group has a sensing group at a distance corresponding to a value of n between 1 and 4.
[0015] According to one aspect, n is between 1 and 3.
[0016] According to one aspect of the invention, the passivating molecule is an aromatic compound substituted by at least one PG and at least one inductive group IG, which are arranged as a structural unit according to the following general formula:
[0017] PG-Ar-IG
[0018] wherein Ar is a substituted aryl group containing C5-C50.
[0019] According to one aspect of the invention, the passivating molecule is an aromatic compound substituted by at least one PG and at least one inductive group IG, which are arranged as a structural unit according to the following general formula:
[0020] PG-Ar-IG
[0021] wherein Ar is a substituted aryl group containing C5-C50.
[0022] According to one aspect of the present invention, the passivating agent comprises one or a combination of molecules having the following general formula:
[0023]
[0024] Where n is 1 to 5,000,000.
[0025] According to one aspect of the present invention, the passivating group is selected from primary amine (-NH2), secondary amine (-NHR), tertiary amine (-NR2), ether and hydroxyl (-OR(H)), sulfhydryl and thiol (-SR(H)), carbonyl (C=O), phosphine (PR3), phosphine oxide (P=O), carboxyl (-COOR(H)), sulfoxide (S=O), sulfone (O=S=O), or any Lewis base functional group, wherein R is an alkyl chain or an aromatic group.
[0026] According to one aspect of the present invention, the sensing group is selected from O, S, F, Cl, Br, I and N.
[0027] According to one aspect of the present invention, the sensing group is selected from cyano (-CN), nitro (-NO2), carbonyl (C=O), carboxyl (-COOR(H)), sulfoxide (S=O), sulfone (O=S=O), amide (-CONH2), acyl chloride (-COOCl), sulfoxide (S=O), and sulfone (O=S=O).
[0028] According to one aspect of the present invention, the passivating agent includes one or a combination of EDEA, ODEA, TDDDA and DDDA.
[0029] According to aspects of the present invention, the optoelectronic device is a photovoltaic device, a laser device, a photodetector, an X-ray detector or a light emitting diode.
[0030] The method for manufacturing an optoelectronic device according to the present invention comprises the following steps:
[0031] - providing a perovskite precursor;
[0032] - providing a passivating agent or a combination of passivating agents doped into the perovskite precursor;
[0033] -Perform surface treatment of perovskite film;
[0034] - performing a passivating molecular vapor treatment; and
[0035] -Incorporated into anti-solvent.
[0036] Thanks to the present invention, the interaction between defect sites in perovskites and passivating functional groups (such as –NH2) can be greatly improved. As a result, non-radiative losses in perovskite semiconductors are greatly reduced, which allows to improve the performance of perovskite optoelectronic devices. In particular, one advantage of the present invention is that it allows to prepare perovskite LEDs with exceptionally high EQE up to 21.6%, which is comparable to the best solution-processed LEDs with organic and quantum dot semiconductors.
[0037] Another advantage is that the perovskite LED with effective passivation leads to a slow current efficiency roll-off, which is around 200 mA cm -2 The OLEDs maintain a high EQE of 20.1% and a wall-plug efficiency of 11.0% at high current densities, making them more attractive than the most efficient organic and quantum dot LEDs at high excitation.
[0038] The inventors have recognized that effective passivation as disclosed herein can improve the operational lifetime of perovskite optoelectronic devices, such as LEDs.
[0039] In the following, the invention will be described in more detail, by way of example only, with reference to the accompanying drawings, with respect to non-limiting embodiments of the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a schematic diagram of the inductive effect utilized in an embodiment of the present invention;
[0042] Figure 2 is the structure of the candidate passivator under investigation;
[0043] Figure 3 is the average EQE peak versus ΔE of PeLEDs treated with candidate passivants. adA graph of the dependencies of ;
[0044] Figure 4 is a schematic diagram of a PeLED according to the present invention;
[0045] Figure 5 is a schematic diagram of a photovoltaic device according to the present invention;
[0046] Figure 6 : PeLED structure, performance and perovskite film characteristics: (a) Molecular structure of HMDA and EDEA, (b) high angle annular dark field (HAADF) cross-sectional image (left, scale bar 500nm) and magnified image (right, scale bar 100nm) of EDEA-treated device with indium tin oxide (ITO) / ethoxylated polyethyleneimine (PEIE): modified zinc oxide nanocrystals (ZnO:PEIE) / perovskite / poly (9,9-dioctylfluorene-co-N-(4-butylphenyl) diphenylamine) (TFB) / molybdenum oxide (MoO3) / Au structure. Representative device characteristics of optimized control device and PA-treated (HMDA, EDEA) devices: (c) EL spectra at 2.5V; (d) EQE-J curves; (e) current density-voltage-radiance (JVR) characteristics. (f) TOF-SIMS measurement of EDEA-treated perovskite film on ITO / ZnO:PEIE substrate (25%), showing unfragmented molecular ions (M + =EDEA + ) and fragment molecular ions ([M-NH3] + and [MH] + ). (g) ATR-FT-IR (NH stretching) for EDEA and PbI2:EDEA mixture. (h) XRD patterns for control film, EDEA (25%) treated film and HMDA (25%) treated film on ITO / ZnO:PEIE substrate. α and # represent the diffraction peaks corresponding to α-FAPbI3 and ITO, respectively;
[0047] Figure 7 : Top view SEM images of perovskite films according to the present invention, (a) control perovskite films prepared with and without anti-solvent (AS) treatment. b, c: EDEA (b) treated perovskite film and HMDA (c) treated perovskite film, wherein the PA content varies from 10% to 30%; the scale bar of the image is 200nm;
[0048] Figure 8: (a) Temperature-dependent (320-240K) capacitance-frequency plots for control, HMDA-treated, and EDEA-treated devices. (b), (c): Trap density inferred from room-temperature Cf plots for control (b) and HMDA-treated (c) samples, (d) Fluence-dependent PLQY. (e) PL lifetime detected by time-correlated single photon counting (TCSPC). The excitation density used for TCSPC measurements is about 10 15 cm -3 ;
[0049] Fig. 9 : Dependence of EL performance on the passivation effect determined by hydrogen bonding, (a) Molecular structures of selected PAs (ODEA, TDDDA, DDDA), the letters shown in the chemical structures are intended to highlight the different lengths of the carbon chains between N and O atoms, (b) Average EQE peaks versus ΔE of PeLEDs from various PA treatments ad , each value is the average of 60 devices, (c) histogram of peak EQE of control and ODEA-treated devices, device characteristics of the best performing ODEA-treated device, (d) JVR characteristics, (e) EQE and wall-plug efficiency as a function of current density, (f) EQE and wall-plug efficiency of control and ODEA-treated devices at 25 mA cm -2 Steady-state EQE under
[0050] Fig.10 : Based on quasi-2DPEA2FA2Pb3I with and without EDEA surface treatment (0.1 vol % in chlorobenzene) 10 Representative device characteristics of perovskite films, (a) EL spectrum at 2.5 V, (b) JVR, c J-EQE, where Pb 2+ The concentration is 0.11M;
[0051] Fig.11 : Representative device characteristics of FAPbI3 films passivated by HMDA (ac) and FAPbI3 films passivated by EDEA (df). (a), (d) EL spectra at 2.5 V. (b) €, JVR. c, f: J-EQE, the perovskite layer is prepared from precursors with a feed ratio of FAI:PbI2:PA=2:1:x, x=10%, 20%, 25%, 30%), Pb 2+ The concentration is 0.13M;
[0052] Fig.12: Representative device characteristics of FAPbI3 films passivated by ODEA (ac), FAPbI3 films passivated by TTDDA (df), and FAPbI3 films passivated by DDDA (gi) at various PA feed ratios. (a), (d), (g) EL spectra at 2.5 V. b, e, h: JVR. c, f, i: J-EQE, the perovskite layer is prepared from precursors with feed ratios of FAI:PbI2:PA=2:1:x, x=10%, 20%, 25%, 30%), Pb 2+ The concentration is 0.13M;
[0053] Fig.13 : Bar graphs of peak EQE from 60 devices at optimized PA feed ratios. (a) HMDA = 20%. (b) DDDA = 25%. (c) EDEA = 25%. (d) TTDDA = 20%. The average EQE peaks for each case are 10.7 ± 0.67% (HMDA), 11.8 ± 0.43% (DDDA), 16.5 ± 0.67% (EDEA), and 16.4 ± 0.61% (TTDDA), respectively. All these devices were made from the same batch of ZnO nanocrystals.
[0054] Details
[0055] The present invention relates to optoelectronic devices based on perovskite materials and methods for their manufacture, the perovskite materials comprising organic passivators for reducing unwanted recombination effects.
[0056] Perovskite is a kind of material that first targets CaTiO3( XII A 2+VI B 4+ X 2- 3) described the ABX3 three-dimensional structure of the compound and named it the perovskite structure. A and B are cations with various valences and ionic radii, and X is an anion. For metal halide hybrid perovskites, the A component is usually a monovalent organic cation, usually methylammonium (CH3NH3 + =MA + ) or carboxamidinium (HC(NH2)2 + =FA + ), atomic cations (usually Cs + ) or a mixture thereof, component B is usually a divalent metal cation (usually Pb2 + Sn2 + or mixture), and the X component is a halogen anion (usually Cl - ,I - Br -or mixtures thereof). Examples include, but are not limited to, MAPbX3, FAPbX3, CsPbX3, MASnX3, FASnX3, and CsSnX3. 0.85 MA 0.1 Cs 0.05 (Pb 0.5 Sn 0.5 )I2Br 0.5 Cl 0.5 combination.
[0057] The B component is usually a divalent metal cation, usually Pb 2+ It can also be selected from Sn 2+ ,Ge 2+ 、Eu 2+ , Cu 2+ , Tb 2 + , Fe 2+ 、Co 2+ 、Zn 2+ , Mn 2+ or they are combined with Pb 2+ Mixtures (such as Sn 2+ / Pb 2+ ) at least one of.
[0058] A more general description of metal halide perovskites is: A'2(ABX3) n-1 BX4. Here n is the number of semiconductor BX4 monolayers within two organic insulating layers (cations A'), where n = ∞ corresponds to the structure of 3D perovskite ABX3, and A' is a large organic ammonium cation such as C4H9NH3 that cannot be incorporated into the 3D perovskite lattice but forms a layered structure or low-dimensional perovskite + (BA) or C8H 12 NH3 + (PEA).
[0059] There are several options to form quasi-2D perovskites or 2D perovskites, such as:
[0060] Pure 2D perovskites, such as BA2PbI4;
[0061] Quasi-2D perovskites (n=2), such as BA2(FA)Pb2I7;
[0062] Quasi-2D perovskites (n=3), such as BA2(FA)2Pb3I 10 , when n=∞, it is 3D FAPbI3 (Part I).
[0063] The present invention relates to both 3D and quasi-2D perovskites.
[0064] Perovskites can also meet A2B1+ B2 3+ X6 structural formula. Here A is a monovalent organic cation or alkali metal ion, including Li + 、Na + , K + , Rb + , Cs + . B1 + It is a monovalent metal ion, such as Ag + , Cu + B2 3+ is a trivalent metal ion, which may be selected from Bi 3 + 、In 3+ , Fe 3+ , Sb 3+ The X component is a halogen anion (usually Cl - ,I - Br - or a mixture thereof).
[0065] The synthesis of perovskite materials is usually carried out in solution, from which perovskites can be obtained in bulk, layered or micro / nanostructured forms.
[0066] In the following, perovskite light emitting diodes (PeLEDs) are discussed as illustrative examples. It will be apparent to those skilled in the art that the present invention is applicable to all optoelectronic devices in which perovskite materials are utilized, including but not limited to photovoltaic devices, such as solar cells; laser gain media in optically pumped lasers or laser diodes, photodetectors and optical communication devices, X-ray detectors, luminescent down-conversion materials or luminescent up-conversion materials in any optoelectronic application, such as sensors, luminescent solar concentrators, and phosphor materials.
[0067] As discussed in the Background section, the main efficiency limitation of solution-processed perovskite optoelectronic devices (e.g., light emitting diodes, LEDs) is trap-mediated non-radiative losses. Defect passivation using organic molecules, molecular passivators (PAs), has been identified as an attractive approach to address this problem. However, this approach has been implemented with only marginal success. Unexpectedly, the inventors have found that weakening of hydrogen bonds between the passivating functional moiety and the organic cations that characterize the perovskite enhances the interaction with defect sites and minimizes non-radiative recombination losses. As a result, exceptionally high-performance near-infrared perovskite LEDs (PeLEDs) with an external quantum efficiency (EQE) of 21.6% can be produced. Moreover, at 200 mA cm -2 At a high current density of 2.3 Å, the passivated PeLED maintains a high EQE of 20.1% and an electro-optical conversion efficiency of 11.0%.
[0068] The PAs utilized according to the present invention are designed to reduce hydrogen bonding ability. In particular, PAs with oxygen atoms within the PAs are used to polarize the passivating amino groups through an inductive effect, reducing their electron donating ability and thus reducing the associated hydrogen bonding ability. This results in enhanced coordination of the PA functional groups to the perovskite defect sites and thus improves the passivation efficiency. As a result, trap-mediated non-radiative recombination is reduced and the electroluminescent (EL) performance of the PeLED is enhanced.
[0069] The perovskite-based optoelectronic device according to the present invention comprises a perovskite material comprising at least one passivating agent (PA) or a combination of passivating agents (PA). The one or more PAs are hydrocarbon compounds comprising at least one passivating group (PG), at least one inductive group (IG) and an alkyl chain. The PA molecules can be conjugated or non-conjugated small molecules, polymers, oligomers.
[0070] Suitable passivating groups are known in the art and include, but are not limited to: -NH2, -NHR, NR3, -OR(H), -SR(H), phosphine, phosphine oxide, sulfoxide (S=O), sulfone (SO2), any Lewis base functional group. R=alkyl or aromatic fused ring. Alternatively, the passivating functional group is an aromatic fused ring containing a heteroatom (O, N, S, B), such as pyridine, pyrrole, imidazole, furan, thiophene and thiazole.
[0071] Suitable sensing groups are known in the art and include, but are not limited to: strongly electronegative atoms, such as O, S, F, Cl, Br, I, N; functional groups that exhibit electron-withdrawing / electron-donating properties that affect the hydrogen bonding ability of the passivating functional group, including -CN, -NO2, C=O, COOR(H), COO-, COONH2, COOCl, S=O, SO2.
[0072] The inductive group (IG) affects the passivating group (PG) and thus affects the hydrogen bonding between the amino group and the FA+ of the perovskite material. Without being bound by theory, this Figure 1 Schematically illustrated in FIG, where IG is O and PG is an amino group (-NH2). IG according to the present invention and the distance measured by the number of carbons n in the carbon chain are selected so that the electron-withdrawing inductive effect of IG (here O atoms) affects PG, thereby polarizing PG electrons toward IG, which thus reduces the electron-donating ability and the associated hydrogen bonding ability of the amino group.
[0073] According to one embodiment of the present invention, PA has structural units according to the following general formula:
[0074]
[0075] wherein n is selected between 1 and 4. The selection of n is based on the peak external quantum efficiency (peak EQE) obtained. A number of PA candidates with different distances n and different numbers of PG groups were tested: HMDA, EDEA, ODEA, TTDDA and DDDA, each of which has a structure exemplified in Figure 2 The experimental details are discussed below. Figure 3 is a graph illustrating the peak EQE of PA candidates. All PA candidates with IG (n<4) outperform the PA candidate without IG (HMDA). As shown in the figure, significant performance enhancements are found for PAs where n becomes smaller, which can be demonstrated by comparing ODEA / TTDDA or EDEA / DDDA. Increasing the number of IGs also affects the peak EQE, as demonstrated by comparing EDEA / ODEA and DDDA / TTDDA. Figure 11-13 The detailed Figure 3 The information summarized in.
[0076] According to an embodiment of the present invention, the conjugation effect provided by the introduction of an aromatic group is utilized in at least one passivating molecule of the PA.
[0077] According to one embodiment, the passivating molecule is an aromatic compound substituted by at least one PG and at least one inductive group IG, arranged as a structural unit according to the following general formula:
[0078] PG-Ar-IG
[0079] wherein Ar is a substituted aryl group containing C5-C50.
[0080] According to one embodiment, the passivating group is a heteroaryl molecule having at least one substituent IG arranged as a structural unit according to the following general formula:
[0081] HAr-IG
[0082] wherein HAr is a heteroaryl group containing C5-C50 and at least one heteroatom selected from N, O, and S.
[0083] According to one embodiment, the passivating agent comprises one or a combination of molecules having the following general formula:
[0084]
[0085] Where n is 1 to 5,000,000.
[0086] According to one embodiment of the present invention, a photovoltaic device is provided based on the above-described optoelectronic device comprising a perovskite material passivated with a passivating agent. Examples of photovoltaic devices include, but are not limited to, solar cells.
[0087] According to one embodiment of the present invention, an optoelectronic device based on the above described perovskite material passivated with a passivating agent provides a laser device or laser application. Laser applications include but are not limited to optical pumping lasers or laser gain media in laser diodes.
[0088] According to one embodiment of the present invention, a photodetector or an optical communication device is provided based on an optoelectronic device comprising a perovskite material passivated with a passivating agent as described above.
[0089] According to one embodiment of the present invention, an optoelectronic device based on the above described perovskite material passivated with a passivating agent provides a device including a luminescent down-conversion material or up-conversion material in any optoelectronic application or an optical communication device.
[0090] exist Figure 4 The structure of the PeLED according to the present invention is schematically illustrated in FIG. 40. The PeLED 40 includes a substrate 41, a transparent conductive material layer 42, an electron transport / injection layer 43 (e.g., a ZnO / PEIE layer), a perovskite layer 44 containing a passivating agent, a hole transport layer (TFB) 45, and an electrode layer (back electrode) 46.
[0091] exist Figure 5 The structure of a photovoltaic device (e.g., a solar cell) according to the present invention is schematically illustrated in FIG. The photovoltaic device 50 includes a substrate 51, a transparent conductive material layer 52, an electron transport layer (e.g., a dense TiO2 or a dense TiO2 / mesoporous TiO2 double layer) 53, a perovskite layer 54 containing a passivating agent, and a hole transport layer (e.g., Spiro-OMeTad) 55, and an electrode layer (back electrode) 56.
[0092] The method for preparing a perovskite-based optoelectronic device according to the present invention comprises the following steps:
[0093] (1) Providing a perovskite precursor.
[0094] (2) Providing a passivating agent or a combination of passivating agents doped into the perovskite precursor.
[0095] (3) Surface treatment of the perovskite film, such as spinning on top of the perovskite film or immersing the perovskite film in a solution containing a passivating agent.
[0096] (4) Passivation molecular vapor treatment, for example, placing the perovskite film in an atmosphere with passivation molecular vapor.
[0097] (5) Incorporation into an antisolvent (e.g., chlorobenzene, chloroform, ether that cannot dissolve perovskite) (e.g., a PA-containing solution that is dropped onto the perovskite film during perovskite film formation).
[0098] An example of this method will be given below.As the skilled person will appreciate, a number of additional steps are taken to produce a particular optoelectronic device, such as a PeLED, such steps following established production techniques and being well known to the skilled person.
[0099] It should be noted that, as will be readily appreciated by those skilled in the art, the elements of the various embodiments described herein can be freely combined with each other unless such combinations are explicitly stated to be inappropriate. For example, according to various embodiments, an attractive combination is to provide a PA with two or more different passivating molecules.
[0100] Results and discussion
[0101] Amino groups have been frequently utilized to passivate perovskite semiconductors due to their coordination bonding to unsaturated PbI6-octahedra. Here, we selected two similar amino-functionalized PAs, namely, 2,2'-(ethylenedioxy)diethylamine (EDEA) and hexamethylenediamine (HMDA) ( Figure 2 ), which have the same alkyl chain length; the difference is that EDEA has two extra O atoms in the chain. The lead formamidinium triiodide (FAPbI3) perovskite layer was deposited by spin casting the precursor in a molar ratio of PbI2:FAI:PA=1:2:x (x=0-30%), where an excess of FAI was used to eliminate the non-perovskite delta phase. We fabricated Figure 6 b PeLED with device configuration depicted in high-angle annular dark-field cross-sectional scanning transmission electron microscopy (HAADF-STEM) image. HAADF-STEM and scanning electron microscopy (SEM) images ( Figure 7 ) all show isolated nano-island features in the perovskite emitter layer. All films were deposited on ITO / ZnO:PEIE substrates. In all cases, the Pb2+ concentration was 0.13 M. All devices showed an EL peak at 800 nm / 1.55 eV ( Figure 6 c) and a low turn-on voltage of about 1.25 V, where the measurements were performed in a glove box filled with N2. Despite the small differences between the chemical structures of EDEA and HMDA, we noticed significant differences in the EQE values of devices treated with these two PAs ( Figure 6 d). The peak EQE of the HMDA treated device is 10.9%, and the peak EQE of the EDEA treated device is 17.9%.
[0102] We performed time-of-flight secondary ion mass spectrometry (ToF-SIMS) on perovskite films treated with EDEA (which has a lower boiling point of 105 °C and therefore represents the harshest sample) ( Figure 6 f) and X-ray photoelectron spectroscopy (XPS) characterization. Compared with the control film, we observed obvious non-fragmented molecular cations of EDEA (C6H 16 N2O2 + =148.1) and linear changes in the C1s, O1s, and N1s core level spectra confirm the adsorption of EDEA molecules in the perovskite film and thus provide an opportunity for passivation. Passivation by coordination bonding was first confirmed by the strong interaction between PbI2 and EDEA, resulting in a change in the solution color of their mixture, followed by the formation of a white precipitate. We further performed attenuated total reflection Fourier transform infrared (ATR-FT-IR) spectroscopy analysis on the EDEA:PbI2 mixture. Figure 6 As shown in Fig. g, the stretching absorption (ν) band of the mixture shifts from –NH2 to a lower wave number relative to that of pure EDEA, indicating that Pb 2+ A coordination bond is formed between –NH2.
[0103] Notably, the molecules used as potential PAs can also be used as template molecules to synthesize low-dimensional perovskites. Therefore, it is worth investigating whether these PAs affect the three-dimensional (3D) crystal structure of FAPbI3. X-ray diffraction (XRD) measurements showed that there were no additional diffraction peaks in the treated perovskite films that were different from those from 3D FAPbI3 ( Figure 6 h).
[0104] The defect physics of the samples was investigated. We reveal that the significant performance improvement of EDEA-treated PeLEDs stems from the significant reduction of defects in the perovskite emitter layer. Thermal admittance spectroscopy (TAS) was performed to probe the trap density and energy depth of the trap states in the PeLEDs ( Figure 8 a). Capacitance versus frequency plots (Cf) showing typical temperature dependence of control and HMDA treated devices. Sub-gap energies derived from the temperature dependent Cf plots show that the trap energy depths for control and HMDA treated devices are 0.40 eV and 0.16 eV, respectively. Figure 8 b and 8c show the trap densities derived from the room temperature Cf plots, giving peak trap densities of 7.8 × 10 15 cm -3 eV -1 and 5.9×10 15 cm -3 eV -1These results indicate a moderate passivation effect of HMDA. In contrast, the EDEA-treated devices show an almost temperature-independent Cf plot, indicating negligible influence of trap states and thus excellent passivation.
[0105] The excellent defect passivation, which leads to significantly reduced trap states in EDEA-treated perovskites, ultimately also results in a greatly enhanced external photoluminescence quantum yield (PLQY) across a large range of excitation energy densities, showing a peak PLQY of 56% ( Figure 8 d). Even at 0.02 mW cm -2 At low energy density of 1.3 Å, the EDEA-treated film still maintains a high PLQY of 40%, consistent with the low defect density. In contrast, the PLQY of the control film and the HMDA-treated film show a strong intensity dependence due to trap-mediated non-radiative recombination. Time-correlated single photon counting (TCSPC) measurements also confirm that trap-mediated recombination in the EDEA-treated sample is low ( Figure 8 e), which shows an extended PL lifetime of 1330 ns compared to the control film (130 ns) and the HMDA-treated film (690 ns).
[0106] After establishing the role of O atoms in influencing the passivation effect, we continued to explore new PAs to both further verify our conclusions and improve device performance. We designed three PAs with different inductive effect strengths ( Fig. 9 a), which are expected to result in different hydrogen bonding abilities and thus different passivation effects. Compared to EDEA, the inductive effect can be increased by introducing an additional O atom (as in 2,2'-[oxybis(ethyleneoxy)]diethylamine (ODEA)) and decreased by increasing the length of the alkyl chain between the N and O atoms (as in 4,9-dioxa-1,12-dodecanediamine (DDDA) and 4,7,10-trioxa-1,13-tridecanediamine (TTDDA)). 32 Among all the PAs with O atoms, the inductive effect in DDDA is the least effective because its N and O atoms are almost isolated from each other, resulting in the strongest hydrogen bonding ability of the amino group. Fig. 9 b shows the change of ΔE ad The average EQE peak of all passivation systems varies. It clearly shows that the EL performance strongly depends on ΔE ad , and thus depends on the hydrogen bonding ability of the amino groups. As expected, ODEA (which shows a ΔE of -0.42 eV) ad The average EQE value) showed the highest average EQE peak value of 19.0±0.8% ( Fig. 9 b and 9c).
[0107] We show the characteristics of the best performing ODEA-treated device, which gives a peak EQE of up to 21.6% ( Fig. 9 e), close to the best organic and quantum dot LEDs. After the device is turned on, the radiant brightness rises rapidly, reaching 308W Sr at 3.3V. -1 m -2 High radiance ( Fig. 9 d). High EQE and low driving voltage lead to an exceptionally high peak wall-plug efficiency of up to 15.8% ( Fig. 9 e). High efficiency at high current density has been challenging in other low-temperature processed LED technologies (e.g., organic LEDs) due to low carrier mobility and strong exciton-induced quenching. Our device achieves high efficiency at 200 mA cm -2 The devices exhibit low efficiency roll-off at high current densities, maintaining high EQE of 20.1% and electro-optical conversion efficiency of 11.0%, which makes them much more efficient than OLEDs and QLEDs at high excitation. In addition, we further tested the operating lifetime (T 50 , the time it takes to reach half the initial radiant brightness). ODEA-treated devices are among the most stable PeLEDs to date 7-10、21 , compared with the control device (at 25mA cm -2 Lower T 50 =1.5h) compared to 25mA cm -2 The following shows a long life of 20h ( Fig. 9 f). The improved lifetime may be due to reduced Joule heating due to high efficiency or to suppression of ion migration due to low defect density.
[0108] We show that our passivation method is applicable to other perovskite semiconductors, such as quasi-2D perovskites with PEA as large cations ( Fig.10 ). In this case, we prepared PEA2FA2Pb3I 10 A solution of EDEA in chlorobenzene (0.1 vol%) was spun on top of 1% EDEA. We observed a clear EQE increase from 7% to 12%.
[0109] In summary, we have demonstrated highly efficient near-infrared PeLEDs with a peak EQE of 21.6%, representing the most efficient PeLEDs to date. Our devices also show low efficiency roll-off, with a peak EQE of 21.6% at 200 mA cm -2 The high EQE of 20.1% and the wall-plug efficiency of 11.0% are maintained at high current density. Our results indicate a unique opportunity for PeLEDs to achieve solution-processed large-scale LEDs with high efficiency at high brightness.
[0110] method
[0111] Materials: Passivating agents (PA) including hexamethylenediamine (HMDA), 2,2'-(ethylenedioxy)diethylamine (EDEA), 4,9-dioxa-1,12-dodecanediamine (DDDA), 2,2'-[oxybis(ethyleneoxy))]diethylamine (ODEA), 4,7,10-trioxa-1,13-tridecanediamine (TTDDA), ethylene glycol diethyl ether (EGDE) were purchased from Sigma-Aldrich. Formamidinium iodide (FAI) was purchased from Dyesol. PbI2 (beads, 99.999%) was purchased from Alfa Aesar. Poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)diphenylamine) (TFB) was purchased from Ossila. Other materials used for device fabrication were all purchased from Sigma-Aldrich.
[0112] Preparation of perovskite solution: Use dimethylformamide (DMF) as solvent to prepare perovskite precursor (FAI:PbI2:PA molar ratio is 2:1:x, x = 0-30%). First, prepare 10 mg mL -1 PA solution is then mixed with Pb as required 2+ The optimal concentration of PbI2 was 0.13 M. The solution precursor was stirred at 50 °C for 12 h before spin coating. Colloidal ZnO nanocrystals were synthesized by solution precipitation process, details of which can be found in the literature. 1 Found in.
[0113] PeLED fabrication: Indium tin oxide (ITO) glass substrates were cleaned sequentially with detergent and TL-1 (a mixture of water, ammonia (25%), and hydrogen peroxide (28%) (5:1:1 by volume). The cleaned substrates were then treated with UV-ozone for 10 min. A ZnO nanocrystal solution was spin-cast onto the substrate at 4,000 rpm in air for 30 s. The substrates were then moved into a N2-filled glove box. Next, a layer of ethoxylated polyethyleneimine (PEIE) (0.05 wt% in IPA) was deposited at 5,000 rpm and then annealed at 100°C for 10 min. After cooling to room temperature, a layer of ZnO nanocrystals with various PA contents and Pb was spin-coated at 3,000 rpm. 2+ The perovskite film was deposited from a precursor of 1.5 % concentration and then annealed at 100 °C for 10 min. For the control perovskite film prepared by antisolvent treatment, the spin casting rate was 5,000 rpm. In addition, 150 μL of chlorobenzene (CB) was added dropwise after 5 seconds of rotation. From the CB solution of TFB (12 mg mL -1 ) was deposited at 3,000 rpm. Finally, at about 1×10 -7 MoO was deposited by a thermal evaporation system through a shadow mask at a base pressure of Torr.x / Au electrode. The device area, as defined by the overlapping area of the ITO film and the top electrode, is 7.25 mm -2 .
[0114] PeLED characterization: All PeLED device characterizations were performed in a nitrogen-filled glove box at room temperature. Measurements were performed using a Keithley 2400 source meter and a fiber integrating sphere (FOIS-1) connected to a QE Pro spectrometer (Ocean Optics). PeLED devices were tested on top of the integrating sphere and only forward emission could be collected, which is consistent with standard OLED characterization methods. The absolute radiance was calibrated by a standard Vis-NIR light source (HL-3P-INT-CAL plus, Ocean Optics).
[0115] Perovskite film characterization: From X-ray tube (Cu Kα, X-ray diffraction patterns were obtained using an X-ray diffractometer (Panalytical X'Pert Pro) with a 200W Xe lamp as the excitation source. Steady-state PL spectra of the perovskite films were recorded using a fluorescence spectrophotometer (F-4600, HITACHI). Absorption spectra were measured using a PerkinElmer model Lambda 900.
[0116] The spectrometer was used in an ultra-high vacuum (approximately 1x10 -10 X-ray photoelectron spectroscopy (XPS) was performed at 1486.6 eV using a monochromatic Al (Kα) X-ray source. XPS experimental conditions were set so that pure Au4f 7 / 2 The full width at half maximum of the line (at a binding energy of 84.00 eV) is 0.65 eV. All spectra were measured at a photoelectron take-off angle of 0° (normal emission).
[0117] Time-of-flight secondary ion mass spectrometry (TOF-SIMS) measurements were performed on a ToF-SIMS.5 instrument from IONTOF, Germany, using a 25 keV Bi3 + The primary ion beam was operated in spectral mode. A mass resolving power of approximately 6000 m / Δm was achieved. For depth profiling, a 1 keV Cs ion beam with a current of 39.81 nA was used. + The sputtering beam removed material layer by layer in a staggered pattern from a 500 × 500 μm grating area. This grating area was chosen to ensure a flat pit bottom over the 100 × 100 μm area used for mass spectrometry analysis. The position of the ITO substrate interface in the sputtering depth profile is determined by the In2 +Defined as half of the maximum value of the secondary ion count rate.
[0118] H nuclear magnetic resonance (NMR): recorded on a Bruker Ultra Shield Plus 400 MHz NMR system 1 H NMR spectroscopy. All samples were prepared by dissolving 5 mg of FAI in 0.4 ml of dimethyl sulfoxide-d6 (DMSO-d6). For blend samples, 15% EDEA or HMDA (molar ratio compared to FAI) was added.
[0119] Attenuated total reflectance Fourier transform infrared (ATR-FT-IR): ATR-FT-IR spectra were recorded from a PIKE MIRacle ATR accessory with a diamond prim using a DLaTGS detector in a Vertex70 spectrometer (Bruker) at room temperature. The measurement system was kept continuously in a N2 atmosphere. -1 The resolution is between 4000cm-1 and 800cm-1. -1 The spectra were acquired from 30 scans performed between 1 and 20 Hz. The presented spectra were baseline corrected by subtracting a linear baseline across the spectral range.
[0120] Aberration-corrected scanning transmission electron microscopy (STEM): Thin samples for STEM imaging were prepared using a FEI dual-beam FIB Helios workstation equipped with an in-situ micromanipulator and a Pt gas injection system. Final grinding was performed at 3 kV. STEM investigations were performed using a JEOL ARM200F TEM equipped with a spherical aberration corrector at the condenser plane. A semi-convergence angle of 32 mrad was used. High-angle annular dark field (HAADF) and annular bright field (ABF) STEM were recorded with half angles in the range of 68-280 mrad and 7-18 mrad, respectively.
[0121] Energy density-dependent PLQY and time-correlated single photon counting (TCSPC) measurements: Energy density-dependent PLQY is measured by a typical three-step technique using a combination of a 445nm continuous wave (CW) laser, a spectrometer, and an integrating sphere. 5 . TCSPC measurements were performed on an Edinburgh Instruments spectrometer (FLS980) with a 638 nm pulsed laser (less than 100 ps, 0.1 MHz). The total instrument response function (IRF) was less than 130 ps and the temporal resolution was less than 20 ps. For the optimized devices, all perovskite films were deposited on ITO / ZnO:PEIE substrates with the same spin-casting conditions and encapsulated with UV-curable resin and glass slides.
[0122] Transient absorption (TA): The perovskite film sample is installed in a dynamic vacuum (<10 -5 mbar). TA spectroscopy was performed in a transmission geometry. An amplified Ti:sapphire laser (Quantronix Integra-C) produced pulses of about 130 fs at a repetition rate of 1 kHz, centered at 800 nm. A broadband white light probe was generated by focusing the pulses into a thin CaF2 plate, and pump light at 400 nm was obtained in a BBO crystal via second harmonic generation. After interaction with the sample, the probe light was dispersed onto a fast CCD array using a grating spectrometer, enabling broadband shot-to-shot detection.
[0123] The trap density was measured by thermal admittance spectroscopy (TAS). For the device capacitance measurements, we used 0.4M Pb in all cases. 2+ to increase the signal. A sinusoidal voltage with a peak-to-peak value of 30mV generated by a Tektronix AFG 3000 function generator was applied to the device. The current signal of the device was amplified with an SR570 low-noise current preamplifier (Stanford Research Systems) and then analyzed using an SR830 lock-in amplifier (Stanford Research Systems), where the amplitude and phase of the current can be measured. Based on the amplitude and phase of the current signal, the capacitance of the device was calculated using a parallel equivalent circuit model. The capacitance spectrum of the device was measured by scanning the sinusoidal voltage frequency from 0.01kHz to 100kHz in logarithmic steps. A DE202AE closed-loop cryogenic cooler (Advanced Research Systems) was used to control the temperature of the device. The capacitance-voltage curve was obtained by measuring the capacitance when a DC bias voltage was scanned from -0.5V to l.0V. Based on the capacitance spectrum measured at different temperatures, the energy (E ω ) The trap density (N T )distributed:
[0124]
[0125] Where V bi is the built-in potential, W is the depletion layer width, V bi and W are obtained from capacitance-voltage measurements, C is the capacitance measured at angular frequency w and temperature T, k is the Boltzmann constant, and ν0 is the escape attempt frequency, which can be obtained by fitting the characteristic frequency with different T based on formula (3).
Claims
1. An optoelectronic device based on a perovskite material comprising a passivating agent, wherein the passivating agent comprises one or a combination of molecules having the following general structural formula: wherein PG represents a passivating group selected from a primary amine -NH2, a secondary amine -NHR, or a tertiary amine -NR2, wherein R is an alkyl chain or an aryl group; and wherein n is 1 to 5,000,000.
2. The optoelectronic device according to claim 1, wherein the passivating agent comprises one or a combination of EDEA and ODEA.
3. An optoelectronic device based on a perovskite material comprising a passivating agent, wherein the passivating agent comprises one or a combination of TTDDA and DDDA.
4. A photovoltaic device comprising the optoelectronic device according to any one of claims 1 to 3.
5. The photovoltaic device (50) according to claim 4, comprising a substrate (51), a transparent conductive material layer (52), an electron transport layer (53), a perovskite layer (54) containing a passivating agent, and a hole transport layer (55), and an electrode layer (56).
6. A laser device comprising the optoelectronic device according to any one of claims 1 to 3.
7. A photodetector comprising the optoelectronic device according to any one of claims 1 to 3.
8. An X-ray detector comprising the optoelectronic device according to any one of claims 1 to 3.
9. A light emitting diode comprising the optoelectronic device according to any one of claims 1 to 3.
10. The light emitting diode (40) according to claim 9, comprising a substrate (41), a transparent conductive material layer (42), an electron transport / injection layer (43), a perovskite layer (44) containing a passivating agent, a hole transport layer (45), and an electrode layer (46).
Citation Information
Patent Citations
Luminescent halide perovskites, methods, compositions, and devices
US20170283693A1